Genetic Predisposition to Malignant Melanoma in the Population of Batam, Indonesia: A Case-Control Study - Simanjuntak, Lisye Tiur (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Malignant melanoma, an aggressive skin cancer, poses a significant global health challenge. Genetic predisposition plays a pivotal role in its development. This study investigates the prevalence of high-risk melanoma susceptibility genes (CDKN2A, MC1R, and others) in the population of Batam, Indonesia, aiming to contribute to risk assessment, early detection strategies, and targeted interventions. Methods: A cross-sectional study involving 300 participants from Batam was conducted. Genetic analysis of CDKN2A, MC1R, and additional melanoma-associated genes was performed using next-generation sequencing (NGS). Demographic and clinical data were collected through questionnaires and medical record reviews. Statistical analysis assessed the association between genetic variants and melanoma risk. Results: The prevalence of CDKN2A pathogenic variants was 2.3%, and MC1R high-risk variants were found in 15.7% of the participants. Significant associations were observed between the presence of these variants and personal/family history of melanoma. Multiple logistic regression analysis identified specific variants conferring a higher risk of melanoma development. Conclusion: This study provides insights into the genetic landscape of melanoma susceptibility in Batam. The identified prevalence of high-risk variants underscores the importance of genetic testing and personalized risk assessment.